A social capital design for delivering online asynchronous professional development in a MOOC course for science teachers. Issue 7 (25th June 2020) - Yoon, Susan A.; Miller, Katherine; Richman, Thomas; Wendel, Daniel; Schoenfeld, Ilana; Anderson, Emma; Shim, Jooeun; Marei, Amin
Abstract : Purpose: The overarching goal of the research is to understand strategies that can support utility and access to high-quality teacher professional development (PD). This study aims to examine the design and delivery of an online asynchronous course for science teachers using the edX massively online open course (MOOC) platform. The conceptual framework considers three areas of research: high-quality PD characteristics for K12 teachers, the development of social capital and known challenges in MOOC and computer-supported collaborative learning and participation. Design/methodology/approach: This is an empirical mixed-methods study that details the design of the PD course and implementation strategies that instantiate the conceptual framework. The authors collected three data sources from 41 teachers who completed the course. These included post course satisfaction surveys, teacher semi structured interviews and discussion board contributions. Findings: Survey findings revealed high satisfaction among teachers in the areas of overall course design, module construction and delivery and usability of materials in teaching. Interview findings showed positive perceptions of the social capital framing in developing tie quality, trust, depth of interactions and access to expertise. Analyses of discussion board contributions also demonstrated high degrees of information exchange resulting from prompts intentionally constructed to foster collaboration. Practical implications: This study offers a set of strategies to build networked teacher PD communities in asynchronous online PD platforms and shows promising evidence of addressing quality and access issues. Social implications: Designing experiences to build teachers' social capital shows promising potential to support high quality PD that may, in turn, raise the quality of science education for students and classrooms both locally in the US and globally. Originality/value: The conceptual framework provides a novel approach to theorizing and operationalizing best practices for teacher PD and online participation.